Empowerment Model of Dairy Farmers in Providing Animal Feed Logistics During the Long Drought in Boyolali Regency - Johan Bhimo Sukoco; Luluk Fauziah (Warta LPM, 2023)
Boyolali Regency is one of the largest cow milk producers in Indonesia. This region controls 20% of the national demand for cow’s milk and 72% of the demand for cow’s milk in Central Java. However, Boyolali Regency is very often hit by the drought, which affects the residents’ dairy farms. Farmers have difficulty in fulfilling animal feed logistics, including clean water and green feed sourced from grasses. Ironically, the farmers have to sell some of their dairy cows to cover the operational costs incurred for other cattle. This study aims to design an empowerment model for dairy farmers in providing animal feed logistics during drought due to a long drought in Boyolali Regency. This study is a qualitative descriptive study. This research is using interviews, observation, and document analysis as their data collection techniques. The data validity technique used in this research is the triangulation method, with an interactive analysis model as data analysis. Farmers complain about the provision of animal feed logistics during drought. Farmers are forced to sell their dairy cows to reduce operating costs. Some farmers buy clean water through a 6.000-liter water tank truck for IDR 300,000 per tank, the estimate is that it can be used for the fulfillment of clean water of approximately 10 heads of dairy cows, or about 10 days. Dairy farmer empowerment model needs to be designed by mapping the logistics needs of animal feed during drought. Clean water assistance from the government is not sufficient for farmers' needs, and the fulfillment of green feed has not been touched by government programs. Therefore, the design of this empowerment model requires deep involvement from the government in empowering farmers to have empowerment in dealing with drought.